ANALYSIS OF MICROALGAE CARBON CAPTURE IN EXHAUST GAS FROM A SINGLE CYLINDER ENGINE IN A FLAT PANEL MODEL DESIGN - Muhammad Ersa Abdullah; Boni Sena; Hendra Nur Arifin; Novela Thresia Pandiangan (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2026)
Carbon dioxide (CO₂) emissions from gasoline engines are one of the contributors to greenhouse gases in the atmosphere. Single-cylinder gasoline engines widely used in motorcycles produce exhaust gases containing CO₂ which has the potential to be used as a carbon source for microalgae. This study aims to analyze the potential for CO₂ absorption from single-cylinder gasoline engine exhaust gases using microalgae in a flat-panel photobioreactor through a mathematical modeling approach. The research method was carried out by determining engine parameters and microalgae kinetic parameters based on literature studies, then calculating exhaust gases and modeling CO₂ absorption using a mass balance, gas-liquid mass transfer, and the Monod model of microalgae growth kinetics. The calculation results show that the engine produces a CO₂ mass rate of approximately 1.545 × 10⁻³ kg/s. The analysis results indicate that microalgae have the potential to utilize CO₂ as a carbon source for biomass growth in a photobioreactor system.